Riba Dalam Persepektif Al-Quran dan Relevansinya Terhadap Mata Uang - Alfian Dani (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2022)
Riba is a social problem in society that has a negative impact on the economy of society in this contemporary era. Along with the times, the medium of exchange developed which in classical times only used nuqud or what was commonly called gold and silver which in the end also had to be reviewed. From this problem, the writer examines the issue of usury and its contextualization with currency. The results of the study conclude that what is meant by usury is additions that are signaled by people who have assets to people who borrow their assets (the money), because of the postponement of the promise of payment by the borrower from a predetermined time. While the Qur'an which talks about the law of usury, the first Qur'an only orders to leave the practice of usury until the last one is a firm command about the prohibition of usury. While the relevance of usury with currency has in common, namely as a medium of exchange that both have the value of usury.